2016
DOI: 10.1016/j.celrep.2016.11.076
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Release from Stores Inhibits GIRK

Abstract: Summary Synaptic transmission is mediated by ionotropic and metabotropic receptors that together regulate the rate and pattern of action potential firing. Metabotropic receptors can activate ion channels and modulate other receptors and channels. The present paper examines the interaction between group 1 mGluR-mediated calcium release from stores, and GABAB/D2 mediated GIRK currents in rat dopamine neurons of the Substantia Nigra. Transient activation of mGluRs decreased the GIRK current evoked by GABAB and D2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…Application of BaCl 2 (100 μM), which blocks GIRK channels (Gantz et al, 2013) produced an apparent inward current (−46.0±10.6 pA, Figure 2A) with GppNHp-but not GTP-containing internal solution (p = 0.0003, n = 9-16, Figure 2C). These data demonstrate that amplifying G protein signaling with GppNHp produces standing currents carried by G protein-gated ion channels, consistent with previous studies (Kramer and Williams, 2016; Loucif et al, 2006). In the continued presence of BaCl 2 , tonic GluD1 R current was measured following application of NASPM (Figure 2D).…”
Section: Resultssupporting
confidence: 92%
“…Application of BaCl 2 (100 μM), which blocks GIRK channels (Gantz et al, 2013) produced an apparent inward current (−46.0±10.6 pA, Figure 2A) with GppNHp-but not GTP-containing internal solution (p = 0.0003, n = 9-16, Figure 2C). These data demonstrate that amplifying G protein signaling with GppNHp produces standing currents carried by G protein-gated ion channels, consistent with previous studies (Kramer and Williams, 2016; Loucif et al, 2006). In the continued presence of BaCl 2 , tonic GluD1 R current was measured following application of NASPM (Figure 2D).…”
Section: Resultssupporting
confidence: 92%
“…α-Syn overexpression reduces D2R-mediated autoinhibition Multiple channels and transporters regulate neuronal activity and intracellular calcium dynamics. Dopamine activation of D2 autoinhibitory receptors on dopamine neurons decreases neuronal activity 16,53,54,56,58 and intracellular calcium dynamics 52,55,[59][60][61][62] . Therefore, we tested the hypothesis that the observed disturbance in neuronal excitability and calcium dynamics in α-syn-overexpressing neurons is due to dysregulation of canonical D2R autoinhibition in these neurons.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests an interesting scenario where GABA-B and D2 receptors may be arranged spatially into overlapping microdomains in which both receptors have access to GIRK channels and the NALCN signaling complex. Likewise, it has been shown that GIRK channels are inhibited by intracellular calcium but enhanced by internal sodium ions (Kramer and Williams, 2016; Wang et al, 2016). This raises the question of whether NALCN and GIRK channels colocalize in a complex with G i/o protein-coupled receptors and whether Na + flowing through NALCN channels potentiates GIRK currents.…”
Section: Discussionmentioning
confidence: 99%